Polydextrose Alleviates Adipose Tissue Inflammation and Modulates the Gut Microbiota in High-Fat Diet-Fed Mice - Hu, Qiuyue; Niu, Yixin; Yang, Yanxia; Mao, Qianyun; Lu, Yao; Ran, Hui; Zhang, Hongmei; Li, Xiaoyong; Gu, Hongxia; Su, Qing (Frontiers in Pharmacology, 2022)
The soluble dietary fiber polydextrose (PDX) is a randomly linked glucose oligomer containing small amounts of sorbitol and citric acid and is widely used in the food industry. However, whether PDX can prevent and treat obesity in high-fat diet (HFD)-fed mice has not been directly investigated, and further studies are needed to better understand the complex interactions among PDX, adipose tissue inflammation and the gut microbiota. In the present study, PDX reduced body weight, fasting blood glucose (FBG), adipose tissue accumulation, adipocyte hypertrophy, serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) levels in HFD-fed mice. Moreover, PDX alleviated serum lipopolysaccharide (LPS) levels and macrophage infiltration in epididymal adipose tissue and resulted in macrophage polarization toward the M2 phenotype. Gut microbiota analysis revealed that PDX promoted the growth of beneficial microbes such as Bacteroides, Parabacteroides, Alloprevotella, Muribaculum, Akkermansia, Ruminococcaceae_UCG-014 and UBA1819 in obese mice, which were negatively correlated with subcutaneous fat, epididymal fat, body weight, FBG, serum TC, HDL-C, LDL-C and LPS levels. Our results indicates that PDX can prevent and treat obesity in HFD-fed mice, specifically in alleviating glucolipid metabolism disorders and adipose tissue inflammation, which may be mediated by modulating the structure of the gut microbiota. Therefore, PDX may become a promising nondrug therapy for obesity.